ANALISIS CEMARAN BAKTERI Coliform PADA PANGAN SEGAR ASAL TANAMAN DI BANDA ACEH MENGGUNAKAN METODE MPN (Most Probable Number) - kamaliah, kamaliah; junita, mela; fajri, cut zahratul; khalida , meutia; mahara, tika; thahira, afifah; fitria, fitria (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
Food safety is a crucial aspect that significantly impacts consumer health and safety, particularly in the consumption of fresh foods such as curly red chilies (Capsicum annuum L.), shallots (Allium cepa), mangoes (Mangifera indica), and cucumbers (Cucumis sativus). This study aimed to detect the presence of Escherichia coli bacteria in these food samples using the Most Probable Number (MPN) method, which includes presumptive, confirmatory, and complementary tests, as well as the IMVIC biochemical test to identify coliform bacteria species. Samples were collected aseptically from various locations in Banda Aceh and tested in a food safety laboratory. The results showed that curly red chilies (3.6/g), cucumbers (9.2/g), and red onion (9.2/g) contained microbial contamination exceeding the national standard safety limit (<3/g), while mangoes (9.2/g) met safety requirements (<20/g). These findings emphasize the importance of strict monitoring and implementation of food safety standards to prevent health risks due to microbial contamination in fresh food products. Furthermore, this study underscores the need to increase awareness and manage food distribution to ensure that products consumed by the public are truly safe and support national food security. Keywords: Food safety; Escherichia coli; Most Probable Number (MPN) method